Comparison of TouchGFX and LVGL Embedded Hardware GUI Libraries - Gökhan İŞNAS; Nurettin ŞENYER (Gazi Üniversitesi Fen Bilimleri Dergisi, 2021)
Embedded hardware screens that provide communication between human and machine are becoming more common every day. User interfaces called GUI (Graphical User Interface) are used on embedded hardware displays to display data about the operation of the device and to control the functions of the device. While the GUI library provides flexibility and convenience to the developer, it also provides convenience to end users. These libraries facilitate the rapid generation of common visuals, speeding up the interface preparation process. GUI libraries are specially designed when used with embedded hardware due to the constraint of processing power . In this study, the LVGL library, which is presented by the open source culture widely used with embedded hardware and continues to be developed, and the free TouchGFX library supported by STMicroelectronics have been examined in depth. First of all, technical and commercial criteria were determined in the light of the literature review, related forum sites, trend analysis and the information provided by the companies. Then, the minimum system requirement, license status, code generation capability, display component support, performance, interfaces and input options, drawing capabilities, text features, display features, styles, compiler programs, popularity, technical support criteria were compared both of libraries. TouchGFX was founded by Stmicroelectronics and prepares easier interfaces for its own products. LittlevGL is developed by an independent developer community. Both libraries are widely used in embedded hardware displays. While LVGL offers coding-heavy development with C / C ++ language, TouchGFX allows direct GUI editing WYSIWYG (What You See Is What You Get) based development.